Analysis Of Services Standards And Workers Productivity Using Work Sampling Method At Xyz Store - Okta Veza (Engineering and Technology International Journal, 2022)
The industrial era is now getting stricter in terms of job search criteria, so employees must improve consistency and ability to understand the work system well. Population Service is one of the public service organizations that serves the community in managing Identity Cards (KTP), Family Cards (KK). Work performance is one of the key elements in determining the success of the implementation of a service process. One method that can be used in employee performance analysis is the job sampling method. From the research sampling conducted for 5 days, 158 files were received, and the target set was 150. Based on the background above, it is not known whether the employee is productive or not, and how long the employee took to collect data. . To find out the performance of civil service employees at the Batam City Population Service. Based on the calculation of the standard time using the work sampling method with the Westinghouse adjustment factor, the standard time needed to serve the making of a KTP or KK is 3.79 minutes and the total productive is 401 or 93% and the non-productive is 31 or 7%. So that it can be said that the performance of public service employees at the Batam City Population Service Office is included in the productive group.